1996
DOI: 10.1093/ndt/11.7.1299
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, fibrinolysis and fibrinolysis inhibitors in haemodialysis patients: contribution of arteriovenous fistula

Abstract: In addition to systemic derangements of haemostasis in ESRD patients, AVF individually might have a substantial role in the modulation of coagulation and fibrinolytic cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…[3][4][5] This is due to increased plasma concentrations of fibrinogen, PAI-1, PAI-1 to tPA ratio, and the activity of coagulation factor VII, and decreased plasma tPA concentration and the activity of protein C. [4][5][6][7][8][9][10][11][12][13][14] Hypercoagulability is a major cause of complications in hemodialysis patients, leading not only to possibly fatal complications such as ischemic heart disease or stroke, but also to thrombus formation in arteriovenous fistulas. [3][4][5]15 In our study, L-carnitine supplement cause a 98 mg/dL decrease in plasma fibrinogen concentration and this reduction was significant as compared to the placebo group. We found no research in available literature about the effect of L-carnitine supplement on plasma fibrinogen concentration to be compared with the results of our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[3][4][5] This is due to increased plasma concentrations of fibrinogen, PAI-1, PAI-1 to tPA ratio, and the activity of coagulation factor VII, and decreased plasma tPA concentration and the activity of protein C. [4][5][6][7][8][9][10][11][12][13][14] Hypercoagulability is a major cause of complications in hemodialysis patients, leading not only to possibly fatal complications such as ischemic heart disease or stroke, but also to thrombus formation in arteriovenous fistulas. [3][4][5]15 In our study, L-carnitine supplement cause a 98 mg/dL decrease in plasma fibrinogen concentration and this reduction was significant as compared to the placebo group. We found no research in available literature about the effect of L-carnitine supplement on plasma fibrinogen concentration to be compared with the results of our study.…”
Section: Discussionsupporting
confidence: 54%
“…[4][5][6][7][8][9][10][11][12][13][14] Hypercoagulability is an important risk factor for thrombosis and its complications such as ischemic heart disease, stroke, and vascular access failure in hemodialysis patients and contributes substantially to high mortality in this population. [3][4][5]15 L-Carnitine has largely been studied and is also frequently used in hemodialysis patients, but according to the available literature, no study investigated the effects of L-carnitine supplement on plasma coagulation (including fibrinogen, coagulation factors V, VII, IX, and PAI-1) and anticoagulation (such as protein C and tPA) factors in hemodialysis patients. Only one study in patients with peripheral vascular diseases showed that L-carnitine supplement could cause an increase in plasma tPA and a decrease in plasma PAI-1.…”
Section: Introductionmentioning
confidence: 99%
“…The most reproducible coagulation abnormalities are high levels of fibrinogen and factor VIII, which have been identified as independent biomarkers of renal insufficiency and cardiovascular events [30][31][32]. In our series of patients, factor VIII and fibrinogen levels were significantly higher in hemodialysis patients than in controls, whereas factor VII and factor IX levels were similar in patients and controls.…”
Section: Discussionmentioning
confidence: 50%
“…Study explored the correlation between baseline FMD and subsequent change in the diameter of the artery and vein at 3 months after AVF creation and found a positive correlation. Erdem et al discovered that during haemodialysis, turbulent flow, intraluminal pressure, and regular needle insertion caused endothelial damage, which led to haemostatic activation in AVF [46]. Wakefield et al's study indicated that thrombus development and blood clotting could be stimulated by higher levels of factor V, plasminogen activator inhibitor-1, tissue factor, and von Willebrand factor, as secreted by a dysfunctional venous endothelium [47].…”
Section: Endothelium Dysfunction and Avf Maturationmentioning
confidence: 99%